Detection of adult-plant resistance to Puccinia triticina in a collection of wild Triticum species - Snyman, J.E; Pretorius, Z.A; Kloppers, F.J; Marais, G.F (Genetic resources and crop evolution, 2004)
Three hundred and fifty three Triticum accessions, several also classified as Aegilops and comprising 13 diploid, tetraploid or hexaploid species, were screened for seedling and adult-plant resistance to Puccinia triticina Eriks. using a mixture of pathotypes UVPrt2, 3, 9 and 13. Seedlings were spray-inoculated with a suspension of freshly collected urediospores in distilled water containing Tween 20 seven days after planting. Infection types (ITs) were scored 10 days post-inoculation (d.p.i.). Fully expanded flag leaves were inoculated and ITs and leaf rust severity were scored 16 d.p.i. One hundred and eighty two of the accessions were resistant to moderately resistant in the adult stage, whereas 126 were resistant or moderately resistant as seedlings to the pathotype mixture. Hypersensitive adult-plant resistance was particularly apparent in lines of T. timopheevii, T. sharonense, T. longissimum, T. searsii and T. turgidum. In T. turgidum, which comprised 272 accessions, approximately 44% of the adult plants were resistant to moderately resistant compared to 28% of the seedlings. The expression of these adult-plant resistances varied between hypersensitive flecking of flag leaves, and small pustules commonly associated with chlorosis and/or necrosis of leaf tissue. Partial resistance, expressed by small pustules without any apparent chlorosis, was observed in species such as T. tauschii, T. turgidum ssp. durum and T. turgidum ssp. pyramidale.